Correlation Between Pre-Chemotherapy AMH Level, Menstrual Status, and Prediction of Ovarian Function Recovery after FAC Chemotherapy AMH in Breast Cancer Patients - Abdurahman, Maman; Rizki, Kiki Ahmad; Pringadi, Adi Zufron (Faculty of Medicine, Universitas Padjadjaran, 2023)
Around 52.6% of women aged <50 years in Indonesia are diagnosed with breast cancer. One of the chemotherapy regimens with a toxicity effect on reproductive function, especially ovarian follicles, is 5-fluorouracil-doxorubicin-cyclophosphamide (FAC). Anti-Mullerian Hormone (AMH) is a biomarker that can be used to assess the ovarian function. This study aimed to determine the correlation between pre-chemotherapy AMH serum level, menstrual status, and whether the AMH serum level can predict ovarian function recovery in pre-menopausal women receiving FAC chemotherapy. This was an analytical observational study with a prospective cohort design performed in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, during 2021-2022. Data were analyzed using correlation analysis. Subjects were breast cancer patients aged ≤45 years, still of reproductive age, with no prior history of chemotherapy, and were undergoing the FAC chemotherapy. All 32 patients who met the inclusion criteria were included in this study. There was a significant difference (p 0.0001) between pre- and post-6 cycles of chemotherapy AMH levels. Post-6 cycles of chemotherapy showed lower AMH levels. There was a high correlation (p 0.0034) between pre-chemotherapy AMH level and menstrual status six months after six cycles of chemotherapy. The correlation test between post-chemotherapy AMH level and menstrual status showed a non-significant result. Thus, there is a high statistical correlation between pre-chemotherapy anti-Mullerian hormone levels in pre-menopausal women with breast cancer and the menstrual status after FAC chemotherapy which demonstrates that the AMH level could also be used to predict ovarian function recovery.